Modeling of domestic water consumption for Kuching - Tero, Philip Lajang (Universiti Malaysia Sarawak, (UNIMAS), 2001)
Domestic water consumption is growing every year for Kuching since the beginning of the service made available in late 1800s. This trend is very pronounced from the early 1980s and the yearly increase may not be sustainable for very much longer since our current sources of raw water supply are almost at their peaks safe yield for the catchments. It should be a concern for us that this trend be kept checked so that the quantity can be stretched further-longer period wihout having to modify the catchments and to cater for a bigger population.This can only be achieved if consumption is kept to the 'needs' level of 160 litres per day/person.